Musical Politics: Protest and Dissent in Aotearoa New Zealand - Alison Stevens Booth (DINÂMIA’CET – IUL, Centre for Socioeconomic and Territorial Studies, 2021)
Popular songs play an important role in mobilising political campaigns by creating platforms for voices of protest and dissent in the discussion of significant issues that questions those in power. This research considers the role songs of protest and political dissent have played over the past 60 years of Aotearoa New Zealand’s postcolonial history. Political messages have been embedded in musical texts reflecting the region’s unique historical and cultural development, especially the positioning of its Pacific peoples (indigenous Māori and immigrants from other Pacific Islands) in issues and processes of political protest. In the 1960s and 1970s, when global human rights movements were gaining traction, in Aotearoa intense feelings over inequities and injustices manifested themselves in song. Māori land rights, sporting relations with the apartheid regime in South Africa and the programme of nuclear testing pursued by the French in the Pacific were all issues of major concern, provoking marches, occupations and boycotts. The social reforms and domestic processes experienced in the separation from Britain (1947) included a ‘coming out’ of difference and dissent and a ‘coming in’ of new cultural influences into the music industry by new waves of migration and the birth of the local recording industry (1960–1986). This case study features 17 representative recordings that cover a range of themes (racism, land rights, nuclear tests, climate change and political discontent) that attracted media attention and public debate. The results presented show how protest songs in Aotearoa continue to play an important role in mobilising political campaigns in the Pacific.